The impact of education level and socioeconomic status on the association between depressive symptoms and memory in an older population in Latin America: An exploratory analysis from the Brazilian Longitudinal Study of Aging (ELSI-BRAZIL) - Karla Loss; Wilson Fandino; Bassel Almarie; Blanca Bazan-Perkins; Julia Minetto; Nadine Aranis; Thiago Monaco; Aisha Aladab; Kevin Pacheco-Barrios; Felipe Fregni (Elsevier, 2024)
Purpose: The globally increasing older population raises concerns about age-related conditions, including cognitive impairment and depressive symptoms. In Latin America, nearly one-third of the population is affected by either of these conditions. However, data investigating the association between cognitive impairment and depressive symptoms, particularly in Brazil, are limited to small-scale studies that have not carefully examined the critical effects of variables such as education level and socioeconomic status on this relationship. We aimed at exploring this association in a representative population-based cohort. Methods: We used the Brazilian Longitudinal Study of Aging (ELSI-BRAZIL) database to examine the relationship between depressive symptoms and cognitive impairment in Brazilian older adults, adjusted for potential confounders. Direct acyclic graphs and multivariable linear regression were used to build our model. Depressive symptoms were measured using a short version of the Center for Epidemiologic Studies Scale (CES D-8), and combined memory recall test as a surrogate of cognitive impairment. Results: The study included 8280 participants. Only education level was identified as a confounder for the relationship between memory loss and depressive symptoms. After adjusting for age, sex, and education level, there was strong evidence for a negative association between depressive symptoms and memory performance. For every 5-unit increase in the CES D-8 score, there was a reduction in memory capacity, translating to a loss of approximately one word in the combined words recall test (mean − 0.18, 95% CI -0.22; −0.15, P < 0.001). In addition, we found strong evidence for an interaction between socioeconomic status and depressive symptoms. Subjects belonging to medium socioeconomic status (SES) showed more pronounced memory decline, when compared to those with lower SES (mean − 0.28, 95% CI -0.42 to −0.14, P < 0.001). Conclusions: In adults aged over 50, after adjusting for sex, age, and educational level, a 5-unit increase in CES D-8 score is associated with loss of one point in the combined memory recall test. This association seems to be confounded by educational level and significantly modified by socioeconomic status.